Discovering candidate genes that regulate resin canal number in Pinus taeda stems by integrating genetic analysis across environments, ages, and populations. Issue 2 (30th September 2014) - Westbrook, Jared W.; Walker, Alejandro R.; Neves, Leandro G.; Munoz, Patricio; Resende, Marcio F. R.; Neale, David B.; Wegrzyn, Jill L.; Huber, Dudley A.; Kirst, Matias; Davis, John M.; Peter, Gary F.
Summary Genetically improving constitutive resin canal development in Pinus stems may enhance the capacity to synthesize terpenes for bark beetle resistance, chemical feedstocks, and biofuels. To discover genes that potentially regulate axial resin canal number (RCN), single nucleotide polymorphisms (SNPs) in 4027 genes were tested for association with RCN in two growth rings and three environments in a complex pedigree of 520 Pinus taeda individuals (CCLONES). The map locations of associated genes were compared with RCN quantitative trait loci (QTLs) in a (P. taeda × Pinus elliottii) × P. elliottii pseudo‐backcross of 345 full‐sibs (BC1). Resin canal number was heritable (h2 ˜ 0.12–0.21) and positively genetically correlated with xylem growth (rg ˜ 0.32–0.72) and oleoresin flow (rg ˜ 0.15–0.51). Sixteen well‐supported candidate regulators of RCN were discovered in CCLONES, including genes associated across sites and ages, unidirectionally associated with oleoresin flow and xylem growth, and mapped to RCN QTLs in BC1. Breeding is predicted to increase RCN 11% in one generation and could be accelerated with genomic selection at accuracies of 0.45–0.52 across environments. There is significant genetic variation for RCN in loblolly pine, which can be exploited in breeding for elevated terpene content.